2012
DOI: 10.1143/jjap.51.02bh01
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of MnAs Nanoclusters Embedded in GaAs Nanowires by Metal–Organic Vapor Phase Epitaxy

Abstract: The authors report on the fabrication of MnAs/GaAs hybrid nanowires by combining selective-area metal–organic vapor phase epitaxy of GaAs nanowires and “endotaxy” of MnAs nanoclusters. MnAs nanoclusters are embedded in the six ridges of hexagonal GaAs nanowires as a result of endotaxy. From the cross-sectional characterizations by transmission electron microscopy, the average width of MnAs nanoclusters with the hexagonal NiAs-type crystal structure and the average depth in GaAs nanowires are estimated to be ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 33 publications
6
15
0
Order By: Relevance
“…The nanowires themselves show no traces of Mn within the EDX detection limit. We also do not observe any sign of endotaxy as, for example, observed for (Ga,Mn)As and (In,Mn)As nanowires grown by metal–organic vapor phase epitaxy. , …”
supporting
confidence: 66%
See 1 more Smart Citation
“…The nanowires themselves show no traces of Mn within the EDX detection limit. We also do not observe any sign of endotaxy as, for example, observed for (Ga,Mn)As and (In,Mn)As nanowires grown by metal–organic vapor phase epitaxy. , …”
supporting
confidence: 66%
“…We also do not observe any sign of endotaxy as, for example, observed for (Ga,Mn)As and (In,Mn) As nanowires grown by metal−organic vapor phase epitaxy. 33,34 In the third sample series, we have then grown pure GaAs nanowires of the same length as shown in Figure 1. In contrast to the second series, we have first fully consumed the pure Ga catalyst droplet at the end of the wire growth through crystallization of GaAs 35,36 by providing As background pressure at a substrate temperature of 600 °C.…”
mentioning
confidence: 99%
“…Epitaxial deposition of heteromaterials with a lattice mismatch has been a natural way to synthesize hybrid nanostructures. The lattice mismatch between the NW core and the shell deposited on its surface provides an energetic driving force for the shell surface to spontaneously self-assemble into various nanostructures via the Stranski–Krastanov (S–K) mechanism. On cylindrical NWs, self-assembly of Ge QDs via the S–K mechanism was observed by Pan et al and Goldthorpe et al On faceted NWs, the growth of nanorings (NRs) was reported by Paladugu et al and by Uccelli et al, and growth of QDs was reported by Uccelli et al and Yatago et al In ref , it was observed that the formation of InAs QDs on both facets and ridges of the hexagonal GaAs NW, and the formed QDs were aligned in a chain-like fashion along the facets or ridges of the NW. In ref , MnAs QDs were observed to grow at ridges for the 100 nm diameter GaAs NW while on both ridges and facets for the 300 nm diameter GaAs NW.…”
Section: Theoretical Analysesmentioning
confidence: 99%
“…6 The controlled elaboration of NWs with dened composition and morphology through the growth of NW superlattices 7 and heterostructures 8,9 has extended their functionality in a more predicable manner. To fully explore the potential of NW systems, many investigators have turned to the synthesis of articial nanostructures in NW systems, 10 such as quantum dots (QDs) [11][12][13][14] and nanoclusters, 15 to generate fascinating multifunctional properties. Single nanostructures embedded within NWs represents one of the most promising technologies for applications in quantum photonics.…”
Section: Introductionmentioning
confidence: 99%